Taboo in art. Pedagogical reflections - Kwiatkowska-Tybulewicz, Barbara (Granice tolerancji w sztuce i w wychowaniu, 2020)
The article focuses on the issue of breaking taboo in art. Starting from the concept of taboo and variability of understanding of this word, the article presents the artistic projects in which the artists made attempts to break the taboo. Based on the analysis of areas being subject to taboo in the 21st century by Anna Dąbrowska, the author presents the artistic project that matches to the three groups of taboo created by Dąbrowska: what ceases to be taboo, what is still taboo and new taboo topics in contemporary culture. The author asks about the presence of art which affects social bans in aesthetic education. Reaching for the concept of minor and major introduced by Deleuze and Guattari, the author indicates normative and mutative aesthetic education.